Analisis Kinerja Simpang Bersinyal Jalan Raden Kusno – Jalan A. Djaelani – Jalan Sujarwo di Kabupaten Mempawah - Benhard Siagian; Elsa Tri Mukti; S. Nurlaily Kadarini (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
Population growth and socio-economic activities increase traffic volume, affecting the performance of the Raden Kusno – A. Djaelani – Sujarwo signalized intersection. This study aims to analyze the intersection’s current performance, estimate its condition over the next five years, and formulate alternative treatment strategies. The research data include geometric characteristics, signal timing, vehicle speed, and traffic volume obtained from CCTV recording over a three-day observation period from moning to evening, as well as population and vehicle data for projection. The intersection performance was analyzed using the PKJI 2023 approach and VISSIM simulation. Under current conditions, the intersection operates at LOS E with delays of 45,12 seconds (PKJI 2023) dan 60,56 seconds (VISSIM). In the five-year projection, delays increase to 48,97 seconds with LOS E (PKJI 2023) and 131,29 seconds with LOS F (VISSIM). Modifying the signal from four to three phases with a 70-second cycle improves the current condition to LOS C, with delays of 24,50 seconds (PKJI 2023) and 29,43 seconds (VISSIM). For the five-year projection, adding a continuous left-turn lane results in LOS D with 27,04 seconds (PKJI 2023) and LOS C with 32,01 seconds (VISSIM).